ANALISIS PERAN DUKUNGAN SOSIAL ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN JASMANI SISWA SEKOLAH DASAR - Miqdad Abrar Mustofa; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Tadulako Journal Sport Sciences And Physical Education, 2026)
This study was motivated by the low learning motivation of elementary school students in Physical Education classes, as evidenced by low student participation, lack of confidence when engaging in sports activities, and students' tendency to avoid physical activities considered tiring. This condition is believed to be related to limited parental social support for their children's learning and physical activity. This study aims to analyze the forms of parental social support and their influence on student learning motivation in Physical Education classes. This study used a qualitative method with a case study approach. Participants were selected through purposive sampling, consisting of 15 students, 15 parents, and 1 Physical Education teacher. Data were collected through semi-structured interviews, observation, and documentation, then validated using source triangulation, methodological triangulation, and member checking. The results showed that parental social support includes emotional, instrumental, informational, and appreciative support. Emotional and instrumental support are the most dominant forms of support in increasing student confidence, enthusiasm, and engagement in Physical Education learning. The main findings of this study indicate limitations in informational support due to some parents' lack of understanding of physical education materials, leading children to often ask friends for answers or seek information on their own. This situation is influenced by limited physical literacy, educational background, and family economic conditions in the Sumedang community. This study concludes that parental social support plays a significant role in increasing students' motivation to learn in physical education classes.